2009
DOI: 10.1063/1.3231491
|View full text |Cite
|
Sign up to set email alerts
|

Ortho-para mixing interaction in the vinyl radical detected by millimeter-wave spectroscopy

Abstract: Ortho-para mixing interaction due to the coupling of nuclear and electron spins was detected for the first time by millimeter-wave spectroscopy of the deuterated vinyl radical H(2)CCD. The ground state of H(2)CCD is split by the deuteron tunneling into two components 0(+) and 0(-) separated by DeltaE(0)=1186.794(16) MHz. Rotational levels in the 0(+) and 0(-) states, one being an ortho level and the other a para level, are coupled by the interaction expressed by 0(+/-)mid R:H(')mid R:0(-/+)=(deltaa(F)/2)S(I(1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…To date, the laboratory spectroscopic studies of vinyl radical H 2 CCH , and its deuterated species have been the only observed ortho ↔ para interaction for free radicals. Although the direct ortho ↔ para transitions have not been observed, large energy shifts (∼1.5 MHz) due to the Δ I = 1 interaction were measured.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, the laboratory spectroscopic studies of vinyl radical H 2 CCH , and its deuterated species have been the only observed ortho ↔ para interaction for free radicals. Although the direct ortho ↔ para transitions have not been observed, large energy shifts (∼1.5 MHz) due to the Δ I = 1 interaction were measured.…”
Section: Introductionmentioning
confidence: 99%
“…Although the direct ortho ↔ para transitions have not been observed, large energy shifts (∼1.5 MHz) due to the Δ I = 1 interaction were measured. From the observed shifts, large mixings of 0.097% and 0.0123% were calculated, and the coefficients of the mixing terms (off-diagonal Fermi contact interaction constants, δ a F ) have been determined to be 68.06(53) MHz and 10.63(94) MHz for H 2 CCD and D 2 CCD, respectively. Very large rates for ortho ↔ para conversion of H 2 CCH and its dueterated species by collision have been predicted …”
Section: Introductionmentioning
confidence: 99%